THE BIOGRAPHICAL ACCOUNTS OF TWO ENGLISH LEARNERS FROM KUANTAN SINGINGI RIAU - Masyhur Masyhur (Universitas Negeri Padang, 2015)
This paper reports a biographic enquiry of two tertiary English learners from Kuantan Singingi Riau and seeks to capture the developmental processes of the leamers' Ianguage learning approaches. By sharing their past language learning experiences, the two learners verbalized their struggles in language learning and revealed the deep impact that their learning settings had on their perceptions of self and language leaming. Their adopted leaming approaches, as revealed in their biographical accounts, seem to be extremely exam-oriented and are dependent on the learners' self-will and effort as well as teachers' support and attention. Both learners' accounts suggest that their language learning approaches are influenced by the contextual discourses about learning English, stressful social processes and a sense of threatened self-identity as English major graduates in a highly competitive educational context.